Barbarians, gentlemen and players : a sociological study of the development of rugby football - Dunning, Eric (Sport in the global society., 2005)
First published in 1979, this classic study of the development of rugby from folk game to its modern Union and League forms has become a seminal text in sport history. In a new epilogue the authors provide sociological analysis of the major developments in international ruby that have taken place since 1979, with particular attention to the professionalism that was predicted in the first edition of this text. Sports lovers, rugby fans and students of the history and sociology of sport will find it invaluable. Rugby football is descended from winter 'folk games' which were a deeply rooted.